Simplify the following Boolean function F(x,y,z) = x’y’z’ + x’y + xyz’ +xz to a minimum number of literals using algebraic manipulation and implement

= x’y’z’ + x’y + xyz’ +xz

= x’ (y’z’ + y) + x (yz’ + z)

= x’ [(y + y’) (y + z’)] + x [(y + z) (z + z’)]

= x’ [(1) (y + z’)] + x [(y + z) (1)]

= x’ (y + z’) + x (y + z)

= x’y + x’z’ + xy +xz

= x’y + xy + x’z’ + xz

= y (x’+x) + x’z’ + xz

= y (1) + x’z’ +xz

=y + x’z’ + xz

total answers (1)

start bookmarking useful questions and collections and save it into your own study-lists, login now to start creating your own collections.

= x’y’z’ + x’y + xyz’ +xz

= x’ (y’z’ + y) + x (yz’ + z)

= x’ [(y + y’) (y + z’)] + x [(y + z) (z + z’)]

= x’ [(1) (y + z’)] + x [(y + z) (1)]

= x’ (y + z’) + x (y + z)

= x’y + x’z’ + xy +xz

= x’y + xy + x’z’ + xz

= y (x’+x) + x’z’ + xz

= y (1) + x’z’ +xz

=y + x’z’ + xz

need an explanation for this answer? contact us directly to get an explanation for this answer